PENGARUH TERPAAN MENONTON FILM DUA GARIS BIRU TERHADAP REMAJA TENTANG HUBUNGAN SEKSUAL PERNIKAH - Pratama, Galih; Kamilla, Maura Najya (AT-TAWASUL, 2025)
Film is a communication medium that can create or have an effect on the audience. Films not only function for entertainment, but also as a means of information and education. Therefore, in today's increasingly modern era, we as users of communication media must be wise in choosing what to watch because if we make the wrong choice it will have a bad influence, especially on children and teenagers who are searching for their identity. The film that is the focus of the research is the film Two Blue Lines. In this study, researchers wanted to find out what attitudes teenagers in Ciawi District, Bogor Regency, would have regarding premarital sexual relations after watching the film Two Blue Lines and how big their influence was. This research uses a quantitative approach with data collection techniques using a questionnaire via Google Form to 100 respondents. The sampling technique uses Purposive Sampling Technique. The theories used by researchers are the Stimulus Organism Response (S-O-R) theory, and the Media Exposure Theory. The results of this study show that there is an influence of exposure to watching the film Dua Garis Biru on teenagers regarding premarital sexual relations in Ciawi District, Bogor Regency with a positive correlation level of 1.668 and the film Dua Garis Biru has an influence of 45% on teenagers' attitudes towards premarital sexual relations in Ciawi District, Regency. Bogor